Pengaruh Capital Adequacy Ratio Dan Biaya Operasional Pendapatan Operasional Terhadap Proporsi Non-Performing Loan Pada Kredit Konsumer PT Bank Central Asia (Persero) Tbk Periode 2015-2024 - Revina Mustari Azani; Lisdawati Lisdawati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to determine the effect of Capital Adequacy Ratio (CAR) and Operating Costs to Operating Income (BOPO) on the Proportion of Non-Performing Loans (NPL) in Consumer Credit at PT. Bank Central Asia (Persero) Tbk for the period 2015-2024. This type of research uses quantitative research methods. The research sample is the financial statements of PT. Bank Central Asia (Persero) Tbk for 2015-2024. The analysis techniques used include classical assumption tests, multiple linear regressions, and hypothesis testing using Statistical Package for the Social Sciences (SPSS) 27 for Windows software. The results show that partially CAR and BOPO have a significant effect on NPL, with significance values of 0.033 and 0.046, respectively. Simultaneously, CAR and BOPO have a significant effect on NPL with a significance value of 0.002.